2019
DOI: 10.1055/s-0039-1697019
|View full text |Cite
|
Sign up to set email alerts
|

Administrações Orais do Látex da Hancornia speciosa Gomes não aumentam a neoformação óssea

Abstract: Objective  The present work aimed to evaluate the systemic effect of H. speciosa latex on bone neoformation. Methods  For this, the latex was collected and diluted to 3% and 50%. A total of 28 Wistar rats were submitted to surgery to create a 5 mm diameter defect in the parietal bone. This experiment was conducted in 2 different periods: 1 and 2. For each period, the rats were divided into 3 groups: Control Group, Latex3 Group, and Latex50 Group, which received, respectively, daily administrations of 0.5 mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
0
0
1
Order By: Relevance
“…The histological analysis showed that the oral administration of H. speciosa latex at 50% did not increase the newly-formed bone in the mandibular alveolus or the calvarial defect. These data corroborate other results previously obtained by our team 27 with the oral administration of the latex in another concentration (of 50% and 3%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The histological analysis showed that the oral administration of H. speciosa latex at 50% did not increase the newly-formed bone in the mandibular alveolus or the calvarial defect. These data corroborate other results previously obtained by our team 27 with the oral administration of the latex in another concentration (of 50% and 3%).…”
Section: Discussionsupporting
confidence: 93%
“…A análise histológica mostrou que a administração oral do látex de H. speciosa a 50% não aumentou o osso recém-formado no alvéolo mandibular ou no defeito calvarial. Esses dados corroboram outros resultados que nossa equipe já obteve anteriormente 27 utilizando outra concentração de látex (50% e 3%) de administração oral.…”
Section: Discussionunclassified